(untitled) (Northern International Medical College Journal, 2022)
Crigler-Najjar syndrome (CNS) was first described in 1952 in Maryland, USA as congenital familial non-hemolytic jaundice with kernicterus by Crigler JF and Najjar VA.1 CNS is a rare genetic disorder characterized by abnormalities in bilirubin metabolism and evident by persistent increase of unconjugated bilirubin. During the first days of life, the syndrome clinically manifests as intense unconjugated hyperbilirubinemia without evidence of hemolysis. It consists of two types, type I and type II. Crigler-Najjar Syndrome is mostly autosomal recessive disorder, but variation may occur in the inheritance of CNS II.2 The key pathogenesis is defect in bilirubin conjugation due to complete or partial deficiency of uridine 5’-diphosphate-glucuronosyl transferase (UGT). This enzyme is required for the conjugation and further excretion of bilirubin from the body. In type I CNS the enzyme activity is completely absent and in type II there is partial absence of the enzyme. Therefore, Type I is more severe form and usually fatal with kernicterus at the age of 1-2 years.3-5 TypeII is less severe and has better prognosis. Patients with CN type II suffer from less jaundice, less neurological impairment, and show a fair response to phenobarbitone therapy (serum bilirubin levels decrease by at least 25%).6 Both males and females are equally affected by CNS. The incidence is approximately 1 in 750,000-1,000,000 in the general population.7 Here we report such a rare case. Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 515-517